The Effectiveness of Mathematics Teaching Material Based on Ethnomathematics - Aritsya Imswatama; Hamidah Suryani Lukman (SAINTIS Publishing, 2018)
The study aims to know the effectiveness of mathematics teaching material used based on ethnomathematics toward mathematical solving problem skill and student critical thinking and to know how student activity on mathematics learning by applying mathematics teaching material based on ethnomathematics. Research method applies a quantitative method with post-test only control design research type. Sampling technique applies cluster random sampling. Data collection technique applies documentation, observation, and test method. Data analysis technique applies quantitative data analysis by using t-test. Based on data analysis result, mathematics teaching material based on ethnomathematics proves effective toward solving problem skill and student mathematical critical thinking. Besides, by applying mathematics teaching material can raise student activity.